Upaya Mitigasi dan Adaptasi Perubahan Iklim melalui Media Permainan Anak Atteropoly kepada Anak Usia Sekolah Dasar : Climate Change Mitigation and Adaptation Efforts through Atteropoly Children's Game Media - Winni R.E. Tumanggor; Indra Chahaya; Rossy Nurhasanah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Bogak Village is a coastal village with a waste problem that can contribute to climate change. Instilling waste management knowledge needs to be done with the appropriate method. The purpose of the activity was to apply the Atteropoly game as an early education means regarding waste management for elementary school-age children in efforts to mitigate and adapt to climate change in Bogak Village. The stages were planning and preparation (gathering information on partner problems and compiling educational game instruments), implementation of service activities, and monitoring evaluation. Educational activities through the Atteropoly game were directly carried out on July 6, 2022 to 30 participants of elementary school-age children and two teachers from the Rumah Qur’an Miftahul Jannah. Measuring the success of Atteropoly media used pre-test and post-test, it was found that there was an increase in participants’ knowledge and the average score of 38,33 (pre-test) to 53,00 (post-test). It can be concluded the Atteropoly game increases the elementary school-aged children’s knowledge in Bogak Village. The community service team also gave a set of Atteropoly game tools and segregated trash bins to the village. It is hoped that the Atteropoly game tool can be used to educate the public, especially elementary school-age children in Bogak Village.